APPLICATION OF DISCOVERY LEARNING MODEL IN IMPROVING STUDENTS' CREATIVITY SKILLS IN BADMINTON LEARNING MATERIALS - Rusdi Rusdi; Azhar Ramadhana; Z Arifin (STKIP Muhammadiyah Kuningan, 2024)
The general aim of this research is to determine the effectiveness of implementing the discovery learning model in improving creativity skills in badminton learning material in class XI SMA Negeri 14 Garut. This research used the Classroom Action Research (PTK) method with a sample of 29 class XI IPS 1 students. The instrument used was a movement creativity questionnaire. Analysis of test data shows that the use of the discovery learning model significantly increases student creativity. The results of this research are based on data from pre-cycle, cycle I and cycle II, which includes aspects of fluency, flexibility, authenticity, detail and sensitivity. The average score in the pre-cycle was 69.4, increased to 78.379 in cycle I, and reached 89.3092 in cycle II. The results per component showed significant improvements: fluency from 74.4 (pre-cycle) to 88.85 (cycle II), fluidity from 72.1 to 89.428, originality from 68.9 to 88.85, granularity from 70.8 to 89.231, and sensitivity from 60.9 to 90.192. This increase shows that discovery learning is effective in improving students' creativity skills in badminton material. This research concludes that the implementation of discovery learning can be an effective strategy for increasing student creativity in physical education learning.